The Effect of Design, Brand Image and Personal Selling on Costumer’s Loyalty through Customer’s Satisfaction: A Study on Darbost T-Shirt’s Customers in Jakarta - I Made Adnyana; Iswanto, Heru (HM Publisher, 2021)
The purpose of this research is to study the effect of product design, brand image, and personal selling on customer loyalty through customer satisfaction studies on consumers of darbost t-shirts in Jakarta and to provide suggestions on how PT. Darbost Garment Industri can increase customer satisfaction by increasing the aspects that influence it. For the independent variables: product design (X1), brand image (X2), personal selling (X3), the dependent variable is customer loyalty (Y) and the intervening variable is customer satisfaction (Z). This research approach is quantitative research according to the questionnaire. The sample used was 150 respondents. The results of this study indicate that each of the dimensions of product design, brand image and personal selling directly has a positive and significant effect on customer satisfaction. Customer satisfaction directly has a positive and significant effect on customer loyalty. And from each dimension of product design, brand image and personal selling indirectly affect customer loyalty through customer satisfaction.